Islamic Education in the Formation of Students’ Character: An Analysis of Imam Al-Ghazali’s Thought - Emha Dzia’ul Haq; Sri Adiningsih; Elia Mu’shoda (Khazanah: Journal of Islamic Education and Science, 2026)
This study aims to analyze the development of students’ character and morality through a critical examination of Imam Al-Ghazali’s thoughts on the philosophy of education and their relevance to contemporary educational issues. The study employs a qualitative approach with a critical literature review design focusing on Imam Al-Ghazali’s major works and recent research findings (2020 - 2025) related to character education. This study utilizes a qualitative approach with a descriptive-analytical method. Data collection was conducted through literature review. The data obtained were analyzed using content analysis techniques to interpret the meaning and substance of Imam Al-Ghazali’s educational philosophy. The research findings indicate that Imam Al-Ghazali’s educational concept emphasizes a balance between the mastery of knowledge and the cultivation of noble character. The core of the discussion is that the purpose of education is not only focused on attaining worldly happiness but also happiness in the hereafter. Furthermore, this article examines the moral and ethical values emphasized by Imam Al-Ghazali in the character-building process. The implications of this research provide a conceptual contribution to the development of education, particularly Islamic education in Indonesia, which is oriented toward character, moral, and holistic development.